An assessment of the construct validity of the Child Health Utility 9D-CHN instrument in school-aged children: evidence from a Chinese trial - Mandana Zanganeh; Peymane Adab; Bai Li; Emma Frew (Health and Quality of Life Outcomes, 2021)
Abstract Background Although there is emerging data regarding the psychometric properties of the Child Health Utility-9D instrument, more evidence is required with respect to its validity for use in different country settings. The aim of this study was to examine the construct validity of the CHU-9D-CHN instrument in Chinese children. Methods Baseline Health-Related Quality of Life (HRQoL) and demographic data were collected from children recruited to the CHIRPY DRAGON obesity prevention intervention randomised controlled trial in China. HRQoL was measured using the Chinese version of the CHU-9D instrument (CHU-9D-CHN) and the PedsQL instrument. CHU-9D-CHN utility scores were generated using two scoring algorithms [UK and Chinese tariffs]. Discriminant validity, known-group validity and convergent validity were evaluated using non-parametric test for trend, Kruskal–Wallis test and Spearman correlation coefficient analysis respectively. Results Data was available for 1,539 children (mean age 6 years). The CHU-9D-CHN was sensitive to known group differences determined by the median PedsQL total score. Furthermore, the mean CHU-9D-CHN utility values decreased linearly with increasing levels of severity on each dimension of the PedsQL for emotional and social functioning domains. They decreased monotonically with increasing levels of severity on each dimension of the PedsQL for physical and school functioning domains (p < 0.001). Contrary to studies conducted in Western countries, and although not statistically significant, we found an indication that HRQoL, using both the CHU-9D-CHN and the PedsQL, was higher in children whose parents had lower levels of education, compared to those whose parents were university educated. The correlation between the CHU-9D-CHN utility values using UK and Chinese tariffs, and PedsQL total scores showed a statistically significant moderate positive correlation (Spearman’s rho = 0.5221, p < 0.001 and Spearman’s rho = 0.5316, p < 0.001), respectively. However, each CHU-9D-CHN dimension was either weakly, or very weakly correlated with each of the predetermined PedsQL domain functioning scores. Conclusions Overall, the findings provide some support for the construct validity of the CHU-9D-CHN within a Chinese population aged 6–7 years. However, some uncertainty remains. We recommend future studies continue to test the validity of the CHU-9D in different country settings. Trial registration: ISRCTN Identifier ISRCTN11867516, Registered on 19/08/2015